Metaphorical patterns in Anthropocene fiction. (August 2019) - Caracciolo, Marco; Ionescu, Andrei; Fransoo, Ruben
This article explores metaphorical language in the strand of contemporary fiction that Trexler discusses under the heading of 'Anthropocene fiction' – namely, novels that probe the convergence of human experience and geological or climatological processes in times of climate change. Why focus on metaphor? Because, as cognitive linguists working in the wake of Lakoff and Johnson have shown, metaphor plays a key role in closing the gap between everyday, embodied experience and more intangible or abstract realities – including, we suggest, the more-than-human temporal and spatial scales that come to the fore with the Anthropocene. In literary narrative, metaphorical language is typically organized in coherent clusters that amplify the effects of individual metaphors. Based on this assumption, we discuss the results of a systematic coding of metaphorical language in three Anthropocene novels by Margaret Atwood, Jeanette Winterson, and Ian McEwan. We show that the emergent metaphorical patterns enrich and complicate the novels' staging of the Anthropocene, and that they can destabilize the strict separation between human experience and nonhuman realities.